Factors Influencing Digital Marketing and Digital Payment on Consumer Purchase Behaviour - Tiewul, Monica (International Journal of Applied Research in Management and Economics, 2020)
The issue of whether innovation and technological advancement continually bring new phenomenon remains unpredictable, especially in the financial industry. As technology and digital services continue to ingrain themselves into more aspects of lives, the financial sector has not been immuned. New technology has given way to new services and with new services comes the gradual disruption of the old. This study researched on the influence of digital marketing and digital payment on consumer purchase behaviour in Coburg, Germany. The availability of digital marketing is enabling many companies of all sizes to embrace mobile and data while adopting a ‘cloud first’ approach to redesigning their business models. This brings about the introduction of a new ‘pay-as-you-go’ business model that enables efficiency, low-cost speed to scale and creation of new, richer customer experience. This research sort to examine the impact of digital marketing on consumer purchase behaviour, assess the factors influencing consumer to patronise digital payment and examine the future of digital payment methods. In this research, primary and secondary data are utilised. The data has been analysed using descriptive and multivariate statistical methods like factor loading analysis, correlation, cross tabulation, and chi-square. From this research, it is concluded that the availability of extensive information, variety of products, level of satisfaction and level of education are the most essential factors influencing digital marketing and digital payment and this will lead to an increase in the digital payment methods with more security in the future. Also, bitcoin will not be accepted as a future digital payment method.